Efficient production factors taking into account the risks in shallot: case study in Nawungan Village, Imogiri district, bantul regency, DIY - Sriyadi; Hanifah, Nurul; Heri Isnawan, Bambang; Budiarto; Wan Ibrahim, Nik Rahila (2023)
The risks of shallot farming refer to the failure of production and price due to fluctuating prices. These farming risks cause farmers to be reluctant to take risks. Differences in risk aversion between individuals can lead to disparities in decision-making. This research seeks to analyze (1) the behavior of farmers towards the risks, and (2) the efficient use production factors by considering production risks. The study was undertaken through interviews with farmers and other relevant stakeholders and field observations. The total sample of 100 farmers was taken at simple random. The majority of farmers behaved reluctantly toward the risks. The use of production factors for land area, labor and organic fertilizers in the shallot production function is not yet efficient. While the use of seeds, Urea fertilizer, TSP fertilizer, NPK fertilizer, POSKA fertilizer, Curacron EC pesticide, Score pesticide, Sellestol pesticide and Dithane M-45 pesticide is inefficient. It is time for farmers to be advised to use organic fertilizers and organic pesticides as a substitute for inorganic fertilizers and chemical pesticides.